2023
DOI: 10.1101/2023.01.13.523885
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The apicoplast is important for the viability and persistence ofToxoplasma gondiibradyzoites

Abstract: Toxoplasma gondii is responsible for toxoplasmosis, a disease that can be serious when contracted during pregnancy, but can also be a threat for immunocompromised individuals. Acute infection is associated with the tachyzoite form that spreads rapidly within the host. However, under stress conditions, some parasites can differentiate into cyst-forming bradyzoites, residing mainly in the central nervous system, retina and muscle. Because this latent form of the parasite is resistant to all currently available t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 80 publications
0
4
0
Order By: Relevance
“…Our TgATG9 conditional knockdown mutant can be used in future metabolomic or proteomic studies for this purpose. While several other pathways have been reported to be critical to bradyzoite survival including storage and utilization of amylopectin granules, maintaining structural integrity of the cyst wall, and apicoplast-related functions, our results underscore the importance of autophagy in this stage of T. gondii [8,[63][64][65][66].…”
Section: Discussionmentioning
confidence: 46%
“…Our TgATG9 conditional knockdown mutant can be used in future metabolomic or proteomic studies for this purpose. While several other pathways have been reported to be critical to bradyzoite survival including storage and utilization of amylopectin granules, maintaining structural integrity of the cyst wall, and apicoplast-related functions, our results underscore the importance of autophagy in this stage of T. gondii [8,[63][64][65][66].…”
Section: Discussionmentioning
confidence: 46%
“…Considering that the apicoplast evolved from secondary endosymbiosis (41) and that the zinc finger domain in TgRimM is essential for its function in our study, ApiRimM might facilitate rRNA maturation and proteostasis in the apicoplast. Previous studies on Toxoplasma apicoplast have shown that apicoplast function is essential for the parasite in vitro survival and growth (4244). Moreover, apicoplast-assigned proteins in hyperLOPIT showed a small number of in vitro dispensable proteins (7), also supporting its bare essentiality.…”
Section: Discussionmentioning
confidence: 99%
“…A more recent investigation of Toxoplasma bradyzoites, the persister forms of T. gondii responsible for chronic infections, indicated that the apicoplast is vital for long-term survival of bradyzoites. Interestingly, tissue cysts derived from mutant parasites with a non-functional dynamin-related protein (Drp) display enlarged, reticulated apicoplasts and compromised persistence (51).…”
Section: Discussionmentioning
confidence: 99%